2014
DOI: 10.1111/jan.12553
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis of befriending

Abstract: Abstract. Aim. To report an analysisof the concept of BefriendingBackground.Befriending is anintervention used in a range of nursing, health and social care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…We updated and repeated the searches in April 2016 to see if recent interest in befriending (for example, Balaam, 2015) included consideration of the ability of befriending services to meet the needs and preferences of different groups of older people, as we had concluded that this was largely absent in earlier research.…”
Section: Methodsmentioning
confidence: 99%
“…We updated and repeated the searches in April 2016 to see if recent interest in befriending (for example, Balaam, 2015) included consideration of the ability of befriending services to meet the needs and preferences of different groups of older people, as we had concluded that this was largely absent in earlier research.…”
Section: Methodsmentioning
confidence: 99%
“…The benefits are claimed to include quality of life (Hsiao et al 2012), as well as vocation and altruism (Carter 2014). Rather than imposing their own personal knowledge and truths, nurses can use connected knowing to learn about the patient's beliefs (Lane & Seraficia 2013) and appreciating mutuality can help in the provision of better holistic and community-based support (Balaam 2015). These abstract benefits correspond to the interpersonal and relational focus in many theories of nursing, but in themselves they lack direction for concrete or practical actions.…”
Section: Broadening the Construct: Mutuality In Contextmentioning
confidence: 99%
“…), vocation and altruism (Carter ). Nurses can use connected knowing to learn about the patient's beliefs rather than imposing their own personal knowledge and truths (Lane & Seraficia ), and an appreciation of mutuality can help them provide holistic and community‐based support (Balaam ). These somewhat abstract formulations fit in with the interpersonal and relational focus in many theories of nursing but may frustrate those seeking concrete action or practical implications.…”
Section: Why Social Capital Theory and Mutuality Are Better Together:mentioning
confidence: 99%